The Impact of Cash Conversion Cycle on Firm Profitability of Retail Companies - Ade Rizky; Mega Mayasari (Journal of Applied Accounting and Taxation, 2018)
The purpose of this study is to investigate the impact of Cash Conversion Cycle on firm profitability of retail companies listed in the Indonesian Stock Exchange for the period of 2012-2015.This study use purposive sampling; therefore the data includes is 76 observations covering 19 firms in 4 years period. The hypothesis testing is using panel data regression. The result shows that CCC has negative effect to firm profitability. The short cycle of CCC will increase firm profitability. Firm size and firm age as control variables do not have significant effect on firm profitability. This study limits to Indonesia’s retail company.